2016
DOI: 10.21165/el.v45i1.633
|View full text |Cite
|
Sign up to set email alerts
|

A expressão da pluracionalidade em libras

Abstract: Este artigo descreve o comportamento semântico da duplicação de mão em verbos tipicamente produzidos com uma mão na Língua Brasileira de Sinais (libras). Defendemos que a duplicação de mãos nesses sinais expressa pluracionalidade e argumentamos que um traço que determina a leitura dos verbos pluracionalizados na libras é a direcionalidade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Directional verbs form a sub-type of transitive verbs that shape their movement in order to include the location associated to the participants of the described event. Sanchez-Mendes & Xavier (2016) showed that with directional verbs the only reading available when two hands are used to perform the verb sign is that of a plurality of arguments. For instance, when the directional predicate kiss goodbye is reduplicated, it can only mean kiss goodbye to many people ( 16).…”
Section: Pluractionality In Librasmentioning
confidence: 99%
“…Directional verbs form a sub-type of transitive verbs that shape their movement in order to include the location associated to the participants of the described event. Sanchez-Mendes & Xavier (2016) showed that with directional verbs the only reading available when two hands are used to perform the verb sign is that of a plurality of arguments. For instance, when the directional predicate kiss goodbye is reduplicated, it can only mean kiss goodbye to many people ( 16).…”
Section: Pluractionality In Librasmentioning
confidence: 99%